Description of an intramonocytic haemoparasite, Hepatozoon lainsoni sp. nov. (Apicomplexa: Adeleorina: Hepatozoidae), infecting Ameiva ameiva lizard (Reptilia: Squamata: Teiidae) in northern Brazil - Morais, Rafaela A.P.B.; Rodrigues, Ana Paula D.; Diniz, José Antonio P.; Úngari, Letícia Pereira [UNESP]; O'Dwyer, Lucia Helena [UNESP]; De Souza, Wanderley; Damatta, Renato A.; Silva, Edilene O. (My University, 2024)
Haemogregarine (Apicomplexa: Adeleorina) parasites are considered to be the most common and widespread haemoparasites in reptiles. The genus Hepatozoon (Apicomplexa: Adeleorina: Hepatozoidae) can be found parasitizing a broad range of species and, in reptiles, they infect mainly peripheral blood erythrocytes. The present study detected and characterized a haemogregarine isolated from the lizard species, Ameiva ameiva, collected from the municipality of Capanema, Pará state, north Brazil. Blood smears and imprints from lungs, brain, heart, kidney, liver, bone marrow and spleen were observed using light microscopy and the parasite was genetically identified by molecular analysis. Morphological, morphometric and molecular data were obtained. Parasite gamonts were found in 49.5% (55/111) of the blood smears from A. ameiva, and were characterized as oval, averaging 12.0 ± 0.8 × 5.9 ± 0.6 m2 in size, which displaced the nuclei of parasitized monocytes laterally. Parasite forms resembling immature gamonts were observed in the spleen and bone marrow of the lizards. Furthermore, phylogenetic analyses of 18S rRNA sequences did not reveal gene similarity with other Hepatozoon spp. sequences from reptiles. Thus, morphological and molecular analyses have identified a new species of Hepatozoon parasite, Hepatozoon lainsoni sp. nov., which infects monocytes of the A. ameiva lizard.
Keywords: 18S rDNA; haemoparasite; Hepatozoon; lizard; monocyte; tissue stage